2022
DOI: 10.32718/nvlvet-f9805
|View full text |Cite
|
Sign up to set email alerts
|

Development of technology for receiving enriched sugar

Abstract: Carbohydrates play an important role in nutrition, especially sugar, it is an integral part of many products, both ready and raw. The norm of sugar consumption per day is 25 g (no more than 5 spoons per day). The issue of increasing the biological value of sugar is relevant, as it plays an important role in human nutrition. Almost no one is engaged in the production of enriched sugar in Ukraine, only a few developments of sugar with functional properties are presented. But this topic is quite relevant in the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that fortified sugar contains amino acids, glucose, fructose, vitamin C, and flavonoids [24,25].…”
Section: Development Of Applications For Fortified Sugarmentioning
confidence: 99%
“…Previous studies have shown that fortified sugar contains amino acids, glucose, fructose, vitamin C, and flavonoids [24,25].…”
Section: Development Of Applications For Fortified Sugarmentioning
confidence: 99%
“…Most of the proteins in sour milk cheese are casein. The protein composition of sour milk cheese includes all essential amino acids (Ryzhkova, 2013;Kitchenko, 2014;Lialyk, 2015;Horiuk, 2016;Samilyk, 2017;Lappa et al, 2022).…”
Section: Introductionmentioning
confidence: 99%